Prenylflavonoid Isoxanthohumol Sensitizes MCF-7/ADR Cells to Doxorubicin Cytotoxicity via Acting as a Substrate of ABCB1 - Liu, Ming (Toxins (Basel), 2017)
Isoxanthohumol is a unique prenylflavonoid with the highest content in beer. Isoxanthohumol has multiple bioactivities and has recently received considerable attention in the scientific community. Nonetheless; its effect on drug resistant cancer cells has rarely been studied. In this paper; we investigated the synergistic effect of isoxanthohumol and doxorubicin on doxorubicin resistant MCF-7/ADR cells. Our results showed that isoxanthohumol sensitized the cytotoxic effect of doxorubicin on MCF-7/ADR cells via increased proliferation inhibition and apoptosis stimulation. Molecular mechanism studies further demonstrated that isoxanthohumol inhibited ABCB1-mediated doxorubicin efflux; stimulated the ATPase activity of ABCB1 (ATP-binding cassette sub-family B member 1); and acted as an ABCB1 substrate. Molecular docking results suggested that isoxanthohumol bound to the central transmembrane domain of ABCB1 and its binding site overlapped with the doxorubicin binding site. The present studies demonstrated that isoxanthohumol was a competitive ABCB1 inhibitor which reversed ABCB1-mediated doxorubicin resistance in MCF-7/ADR cells; and therefore could be further developed to help with overcoming ABCB1-mediated drug resistance.